Robert Southey, Politics, and the Year 1817 - Packer, Ian (Romanticism on the Net, 2017)
This article examines Robert Southey’s interactions with both politics and politicians in the year 1817. The publication of the sections of the Collected Letters of Robert Southey covering the period 1815-21 makes possible a much closer and more nuanced examination of how Southey responded to the controversy over the unauthorised appearance of his early radical play, Wat Tyler, and his subsequent condemnation in the House of Commons as a “renegado.” The Collected Letters make clear that Southey’s reaction to these events became entangled with his determination to gather support for his distinctive political programme, which he believed would save the country from revolution. However, Southey’s interventions in the fraught political and cultural debates of 1817 only served to cement his reputation as a particularly reactionary conservative.